Electrographic pattern recognition: A simple tool to predict clinical outcome in children with lissencephaly. (December 2020) - Jauhari, Prashant; Farmania, Rajni; Chakrabarty, Biswaroop; Kumar, Atin; Gulati, Sheffali
Highlights: Electroencephalography pattern recognition aids in diagnosis of Lissencephaly. EEG patterns corelate with clinical outcome better than radiological severity grading in children with Lissencephaly. EEG pattern III is associated with severe developmental delay and drug resistant epilepsy. Abstract: Purpose: To describe and correlate the clinical, radiological and EEG findings in children with lissencephaly. Method: Retrospective record analysis of children with lissencephaly presenting to tertiary health centre in Northern India was performed. Radiological classification and severity scoring were done. EEG findings were categorized into three patterns and its association with clinical severity was studied. Results: Twenty-eight children (males = 17) with lissencephaly were enrolled. Median age at diagnosis was 6.5months (range 3days-3years). Global developmental delay (median social quotient (SQ) = 25 (range15−68) was seen in all; motor deficits in 23 (82 %); epilepsy in 21 (75 %); behavioural problems in 18 (64 %); ophthalmic problems in 17 (61 %); microcephaly in 13 (46 %); feeding difficulty in 12 (43 %). Radiologically, classical Type I lissencephaly was seen in 18(64 %), cobblestone variant (Type II) in 5 (18 %) and microlissencephaly in 5 (18 %). Grade 4 (diffuse pachygyria) radiologic severity was most common (severity grade 1–6); no cases with severity score 5 or 6 were seen. The clinical profile did not correspond with radiological severity grading. EEG pattern recognition revealed pattern I in 14 (50 %); pattern II in 6 (21 %); pattern III in 8 (29 %). Children with pattern III EEG had drug resistant epilepsy and severe developmental delay. No relationship between EEG patterns and radiological severity grading was evident. Conclusion: EEG is better predictor of clinical status and outcome rather than radiological severity grading. EEG pattern III is associated with severe developmental delay and drug resistant epilepsy.